Peran Moderasi Good Corporate Governance Pada Hubungan Kinerja Lingkungan dan Pengungkapan Lingkungna Terhadap Nilai Perusahaan - Bahaswar, Muhammad Raichan; Pramono, Hadi; Amir, Amir; Dirgantari, Novi (E-Jurnal Akuntansi; Vol 35 No 4 (2025)DO - 10.24843/EJA.2025.v35.i04.p17, 2025)
The study aims to empirically examine the relationship between environmental performance and environmental disclosure on firm value with Good Corporate Governance as a moderating variable. The population in this study consists of energy and mining companies listed on the Indonesia Stock Exchange from 2020 to 2023. The sample was determined using the purposive sampling method The data were analyzed using the Moderation Regression Analysis (MRA) technique. The results showed that environmental performance has a significant positive impact, and environmental disclosure does not affect the company's value. Good corporate governance is able to strengthen the relationship between environmental performance and company value, but not the relationship between environmental disclosure and company value. Keywords: Company Value; Environmental Performance; Environmental Disclosure; Good Corporate Governance